Evaluation of osteoclasts’ distribution on the periodontal ligament of rabbits - Carrera, Manoela (2013)
Abstract Objective: assess the distribution and quantity of osteoclasts on periodontal ligament of rabbit’s molars in physiological conditions. Methodology: one hundred and seventy-six histological sections were analyzed, obtained through bone blocks removed from the first molar regions on both sides of the mandible of 44 rabbits. Sections were stained with TRAP technique. Results: osteoclasts were found in 53,98% of the slides and were absent in 46,02%. These cells were usually located on the cervical and median third. Nonparametric Friedman Exact test evidenced a statistically significant difference between the thirds, and Dunn’s a Posteriori test indicated such difference between apical and cervical thirds and apical and median thirds (p<0,05). Conclusion: physiological re-modeling of the alveolar bone occurs when stress generated is sufficient to induce monocytes differentiation in osteoclasts. These cells are more concentrated on the cervical and median thirds due to the direction of the dental movement. Keywords: Osteoclasts. Periodontal ligament. Bone Remodeling